Exploration of Healthcare Professionals’ Stance on the Natural Moral Law (Revista Iberoamericana de Bioética, 2023)
The ethical training of healthcare professionals is essential, especially in the postmodern culture, where human dignity is often neglected. According to Kant, dignity is based on autonomy as the capacity to legislate for self-determination. The secular approach to dignity allows for the establishment of normative guidelines, complemented by Natural Law. Some professionals consider that Natural Moral Law provides a solid framework for bioethics. This study investigates the prevalence of professionals adhering to Natural Moral Law and develops a scale to measure their level of agreement with it. A cross-sectional study was conducted with healthcare professionals, and a frequency analysis of 65 questionnaires was performed. The results showed that most participants took a moderate stance, not fully accepting moral relativism. Overall, participants recognized the importance of ethics in their behavior and decision-making. It was found that Natural Moral Law allows for nuances in clinical practice, guiding it towards respect for human dignity and allowing for intermediate positions towards moral relativism. The existence of moral absolutes and the desire for justice and mutual respect were confirmed. Furthermore, the importance of ethical reflection in science was emphasized to prevent human deterioration.
Keywords: ethics; principlist bioethics; Natural Moral Law